85 A fast refocus; an irish dermatology department in the era of COVID-19. (16th November 2020) - O'Connell, Garret; O'Connor, Cathal; Bourke, John; Murphy, Michelle
Abstract : The arrival of Covid-19 in early 2020 posed a unique challenge for Dermatology, a largely outpatient based and highly visual specialty. We, a large Dermatology Department based in the south of Ireland, recognised that a dramatic reduction in face-to-face interaction must be delivered on a tight timeline to ensure patient and staff safety. The response to a crisis like this required us to refocus on our core objectives; maintaining care and safety for returning patients, whilst also providing continued access for acute and serious new referrals. With the arrival of Covid-19 to Irish shores in late February we immediately moved to telephone clinics for returning patients. Video consultations for new patients were introduced within two weeks. Later we increased the number of 'see-and-treat' surgical lists to manage suspected skin cancers, thereby minimising exposure risk. Our pre-existing photo-advice email service for GP's was re-advertised, which helped us to triage referrals. Meanwhile our multidisciplinary meetings for Melanoma, Dermatology/Pathology and Dermatology/Plastic Surgery were moved to teleconferencing. We employed a 'fail fast, learn fast' approach. By example we soon learned that patients referred with skin lesions are not suitable for video consultation due to video fidelity issues. This led to a successful increase in 'see-and-treat' surgical lists to compensate. As a result of these changes we have managed to maintain our service, an achievement which is demonstrated by our clinic numbers for new and returning patients, our clinical meetings proceed uninterrupted and even unintended benefits, such as a reduction in our 'did not attend' rate (a decreased from 22% pre-COVID to a 'did not answer' rate of 7% during lockdown). Change may be forced, but in the words of Voltaire 'Perfect is the enemy of good'. Through focus, courage and flexibility we weather the storm.